Ultrastructural changes in methicillin-resistant Staphylococcus aureus induced by positively charged silver nanoparticles - Romero-Urbina, Dulce G.; Lara, Humberto H.; Velázquez-Salazar, J. Jesús; Arellano-Jiménez, M. Josefina; Larios, Eduardo; Srinivasan, Anand; Lopez-Ribot, Jose L.; Yacamán, Miguel José (Beilstein Journal of Nanotechnology, 2015)
Silver nanoparticles offer a possible means of fighting antibacterial resistance. Most of their antibacterial properties are attributed to their silver ions. In the present work, we study the actions of positively charged silver nanoparticles against both methicillin-sensitive Staphylococcus aureus and methicillin-resistant Staphylococcus aureus. We use aberration-corrected transmission electron microscopy to examine the bactericidal effects of silver nanoparticles and the ultrastructural changes in bacteria that are induced by silver nanoparticles. The study revealed that our 1 nm average size silver nanoparticles induced thinning and permeabilization of the cell wall, destabilization of the peptidoglycan layer, and subsequent leakage of intracellular content, causing bacterial cell lysis. We hypothesize that positively charged silver nanoparticles bind to the negatively charged polyanionic backbones of teichoic acids and the related cell wall glycopolymers of bacteria as a first target, consequently stressing the structure and permeability of the cell wall. This hypothesis provides a major mechanism to explain the antibacterial effects of silver nanoparticles on Staphylococcus aureus. Future research should focus on defining the related molecular mechanisms and their importance to the antimicrobial activity of silver nanoparticles.
Keywords: electron microscopy; methicillin-resistant Staphylococcus aureus (MRSA); positively charged nanoparticles; silver nanoparticles; Staphylococcus aureus; wall teichoic acids